Effects of the cervical headgear in growing Angle Class II malocclusion patients: a prospective study - Rosa,Anderson Jaña (2020)
ABSTRACT Objective: Evaluate dental and skeletal changes resulting from the exclusive use of the cervical headgear for 15 ± 4 months in the treatment of patients with Class II division 1 malocclusion. Methods: Differences between the beginning (T1) and immediately after the end of the therapy (T2) with the cervical headgear in growing patients (Experimental Group, EG, n = 23) were examined and compared, during compatible periods, with those presented by a group of untreated individuals (Control Group, CG, n =22) with similar malocclusions and chronological age. The cephalometric variables evaluated were: ANB, GoGn.SN, AO-BO, S'-ANS, S'-A, S'-B, S'-Pog and S'-U6 (maxillary first molar). The Shapiro-Wilk and Levene tests were used to evaluate the results. Results: Significant differences were found relative to the ANB, S'-U6, AO-BO, S'-ANS, S'-A, S'-B and S'-Pog variables between T1 and T2 when comparing both groups. No statistically significant variation was found regarding the GoGn.SN angle. Conclusions: The use of cervical headgear promoted distal movement of the maxillary first molars and restricted the anterior displacement of the maxilla, without significantly affecting the GoGn.SN angle.